The matchstick grasshopper genus Warramaba (Morabidae: Morabinae): a description of four new species and a photographic guide to the group - Kearney, Michael R. (Zootaxa, 2018)
Matchstick grasshoppers are a unique and diverse element of Australia’s insect fauna with great potential as a model system for ecological, evolutionary and biogeographical studies. The genus Warramaba comprises four bisexual species. It is of special interest from an evolutionary point of view because two parthenogenetic lineages (the Standard and Boulder-Zanthus phylads of W. virgo) have evolved through hybridization events between two of the sexual species. Despite the extensive genetic and systematic work that has been done on this genus, three of the bisexual species are yet to be formally named (P196, P169 and P125) and no key exists for their identification. Here I formally describe these species, respectively, as W. whitei sp. nov., W. flavolineata sp. nov. and W. grandis sp. nov. and split the parthenogenetic species W. virgo into two distinct species (the addition of W. ngadju sp. nov.). I also provide a photographic guide and key to the identification of all species in the genus.